Minimally Invasive Celiotomy for the Retrieval of Intestinal Foreign Body in a Dog - M. Madeena Begum; M. Ranjithkumar; S. Sunandhadevi; M. Pushpa; M. Balagangatharathilagar (The Indian Veterinary Journal, 2023)
A 1.5 year old intact male Labrador retriever dog was brought to the hospital with a history of chronic vomiting. Clinical examination revealed dehydration. On radiographic evaluation, pet had no abnormalities in the thorax but a radio-opaque non-linear foreign material was noticed in the intestinal loop. The condition was confirmed as intestinal foreign body and surgery was performed under general anaesthesia. A minimally invasive celiotomy was performed with one inch midventral incision and the foreign body was retrieved by enterotomy. The sutures were removed on 5th post-operative day after the complete healing and the animal made an uneventful recovery.